Identification and localization of growth factor genes in the sea cucumber, Holothuria scabra. Issue 11 (November 2021) - Kornthong, Napamanee; Phanaksri, Teva; Saetan, Jirawat; Duangprom, Supawadee; Lekskul, Buranee; Vivattanasarn, Tipok; Songkoomkrong, Sineenart; Jattujan, Prapaporn; Cummins, Scott F.; Sobhon, Prasert; Suwansa-ard, Saowaros
Abstract: The sea cucumber Holothuria scabra is both an economically important species in Asian countries and an emerging experimental model for research studies in regeneration and medicinal bioactives. Growth factors and their receptors are known to be key components that guide tissue repair and renewal, yet validation of their presence in H. scabra has not been established. We performed a targeted in silico search of H. scabra transcriptome data to elucidate conserved growth factor family and receptor genes. In total, 42 transcripts were identified, of which 9 were validated by gene cloning and sequencing. The H. scabra growth factor genes, such as bone morphogenetic protein 2A ( BMP 2A ), bone morphogenetic protein 5-like ( BMP5-like ), neurotrophin ( NT ) and fibroblast growth factor 18 ( FGF18 ), were selected for further analyses, including phylogenetic comparison and spatial gene expression using RT-PCR and in situ hybridization. Expression of all genes investigated were widespread in multiple tissues. However, BMP 2A, BMP5-like and NT were found extensively in the radial nerve cord cells, while FGF18 was highly expressed in connective tissue layer of the body wall. Our identification and expression analysis of the H. scabra growth factor genes provided the molecular information of growth factors in this species which may ultimately complement the research in regenerative medicine. Abstract : Growth factors, Sea cucumber, Holothuria scabra, Gene expression.